Analysis of the acrylamide in breads and evaluation of mitochondrial/lysosomal protective agents to reduce its toxicity in vitro model. (2nd January 2022) - Salimi, Ahmad; Pashaei, Rafat; Bohlooli, Shahab; Vaghar-Moussavi, Mehrdad; Pourahmad, Jalal
Abstract: Acrylamide, as a carcinogenic agent, is formed during food processing. Because of the high number of gastrointestinal cancers in Ardabil City, we hypothesized that probably the amount of acrylamide is high in the traditional breads. Also, due to the human are inevitably subjected to acrylamide, we searched strategies for reducing its toxicity in cellular level. The concentration of acrylamide in Barbari, Taftoon, Sangak, and Lavash breads were 143.5 ± 2.5, 129.4 ± 1.7, 95.2 ± 1.3, and 17.5 ± 2.5 μg/kg, respectively. Mitochondrial/lysosomal protective agents decreased acrylamide-induced oxidative damages. Results indicated acrylamide is high in these breads and mitochondrial/lysosomal protective agents could be a strategy for reduction of its toxicity.